Urban ecology and planning: a necessary convergence - Angeoletto, Fabio Henrique Soares; Fellowes, Mark Dominic Edmund; Essi, Liliana; Santos, Jeater Waldemar Maciel Correa; Johann, Juciane Maria; Leandro, Deleon da Silva; Mendonça, Nathalia Moraes (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2019)
The global and massive urbanization of territories is one of today’s most important ecological phenomena. The standards used in urban growth are vital for the conservation of biological diversity, and also affects the provision of a reasonable quality of life for urban populations. Contrary to the perception held by many biologists and other academics, where cities are sterile environments and the opposite of natural, the recent development of urban ecology, a necessarily interdisciplinary science, shows that cities are heterotrophic ecosystems that need to be planned in a manner that reduces their impacts on the biosphere, and that in parallel increases their ability to sustain biodiversity.